Peran Wakaf Dan Zakat Dalam Meningkatkan Ekonomi Masyarakat Indonesia - Muhammad A.A, Firman; Rosidta, Adina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
Poverty and unemployment are currently complex and serious issues in Indonesia, with one of the primary causes being the unequal distribution of wealth in society. Islam presents a significant potential solution to address these problems through the utilization of zakat and waqf, two concepts deeply rooted in the principles of social justice and economic empowerment. This research aims to analyze the roles of zakat and waqf in improving the economic well-being of Indonesian society, exploring the potential for collecting zakat and waqf funds, and proposing productive waqf management models. The findings of the study reveal the pivotal roles that zakat and waqf play in reducing economic inequality. Zakat can be used to provide direct assistance to those in need and empower the community through small business capital and skills training. On the other hand, waqf has the potential to create long-term investments in economic development by utilizing waqf assets for productive projects that generate employment and income. Additionally, the research highlights the importance of productive and creative management of zakat and waqf funds, including strategic investments in waqf assets. Increasing public awareness of zakat and waqf and fostering collaboration with governmental institutions and communities are identified as key factors in maximizing the potential of zakat and waqf. Educational initiatives and fundraising models, such as conducting fundraising activities at various locations, are also described as crucial steps in achieving economic empowerment and poverty reduction through zakat and waqf. With the right approach, zakat and waqf have the potential to become powerful instruments in alleviating poverty and unemployment in Indonesia, leading to a more prosperous and economically equitable society.